Perovskite Solar Cells: All‐Carbon‐Electrode‐Based Endurable Flexible Perovskite Solar Cells (Adv. Funct. Mater. 11/2018). (12th March 2018) - Luo, Qiang; Ma, He; Hou, Qinzhi; Li, Yingxiang; Ren, Jing; Dai, Xuezeng; Yao, Zhibo; Zhou, Yu; Xiang, Lichen; Du, Huayun; He, Hongcai; Wang, Ning; et al.
Abstract : A durable flexible perovskite solar cell that employs graphene as transparent anode and carbon nanotubes as cathode is successfully developed by Ning Wang, Kaili Jiang, Hong Lin, Zhanhu Guo, and co‐workers in article number1706777 . All‐carbon‐electrode‐based devices exhibit promising efficiency, excellent flexibility, and stability, providing a new avenue for construction of cheap and large‐scale flexible perovskite solar cells.